Wolf rune [compact disc] - Langeland, Sinikka (ECM, 2021)
Wolf Rune, a solo album, casts a new light on the highly personal idiom of Sinikka Langeland, kantele player and folk singer from Finnskogen, Norway's "Finnish forest". Sinikka integrates her own songs among folk hymns, shamanistic rune songs and traditional dance pieces, draws texts from multiple poetic sources, and expands the expressive range of her instruments.